The effect of substance abuse on depression, anxiety, and stress (DASS-21) in epileptic patients - Vahid Farnia; Daryoush Afshari; Nasrin Abdoli; Farnaz Radmehr; Mehdi Moradinazar; Mostafa Alikhani; Behrouz Behrouz; Mehdi Khodamoradi; Negin Farhadian (Elsevier, 2021)
Background: Psychological symptoms are common problems in chronic medical patients who are often overlooked or treated incompletely. Inaccuracy in timely diagnosis and treatment of these symptoms can have important consequences for these patients. Objective: The aim of this study was to investigate the effects of substance abuse on anxiety, depression, and stress in epileptic patients. Methodology: The study population in this descriptive and case-control research consisted of the epileptic patients who referred to Farabi Medical Center in Kermanshah in Iran during 2018-2019. Seventy-nine epileptic patients with a history of substance abuse and 41 epileptic patients with no history of substance abuse were assessed. These selected peoples completed two checklists of the researcher-made demographic questionnaire and the short form of depression, anxiety and stress scale (DASS21). Results: Mean (±SD) age of epileptic patients was 32.8 ± 11.42 years. In epileptic addicted, the lowest and highest seizure rates were observed in opium (0.44), marijuana (0.80) and tramadol (0.67), abusive patients respectively. The single variable and multivariate analysis also showed that after controlling for confounding variables, the DASS21 scale score of 21 questions was 6.02 (0.90-11.15) higher than epileptic patients without substance abuse. Conclusion: The results show that psychological symptoms have an important role in the development of addiction among epileptic patients. Identifying these symptoms in high-risk groups, such as chronic medical patients, can be effective in designing preventive and therapeutic interventions to reduce epilepsy-related problems as well as seizure and substance abuse in these patients.